The discipline of modern mathematics in industrial technical courses in Portugal - Rodrigues, Alexandra Sofia (2026)
The reform movement known as modern mathematics aimed to modernise mathematics education to meet the social, professional, and scientific needs felt after the Second World War. Despite the movement's internationalisation, through collaborative meetings among educational agents from different countries, it was incorporated into national education systems in very different ways. This theoretical essay analyses the constitution of the mathematics discipline in industrial courses of Portuguese technical education during the modern mathematics reform, within the framework of the notion of school knowledge. It concludes that the reform mobilised teachers in industrial education, who reinterpreted international guidelines in light of their previously consolidated teaching knowledge. This appropriation reflected tensions between the valorisation of structuralist abstraction and the need for connection to reality and professional training. Historically, the movement contributed to the redefinition of teachers' professional identities and to the restructuring of pedagogical practices; socially and economically, it translated into an effort to align technical education with the demands of modernisation and the country's industrial development, albeit limited by the regime's hierarchies and political priorities. The extinction of the Technical Schools, after the democratisation of education in 1974, ended this reform cycle, leaving, however, lasting marks on the school culture and curricular organisation of Portugal.